NEW SUBCLASS OF UNIVALENT FUNCTIONS DEFINED BY USING GENERALIZED SALAGEAN OPERATOR - S. B. Joshi; N. D. Sangle (Journal of the Indonesian Mathematical Society, 2009)
"Pdf FIle"DOI : http://dx.doi.org/10.22342/jims.15.2.46.79-89